Employability Capital for Tour Guides at a World Heritage Site - Wakelin-Theron, Nicola (Journal of Education Culture and Society, 2023)
Aim. Employability has gained increased interest after the respective global shocks of 2008 and 2020. The study deepens the theory of employability in relation to a globally significant tourism industry. The aim of the study is to identify the core dimensions of the employability of tour-guides. Method. The study adopted a qualitatively intrinsic case study at a world heritage site (WHS), namely the Maropeng Visitor Centre. The researcher focused on the notion of employability for tour-guides, based on existing research gaps regarding those two central concepts. Results. The study determines the roles and responsibilities of tour-guides so as to align these to the notion of employability capital of tour-guides. Secondly, the study probed how higher education institutions (HEIs) should contribute to tour-guides’ employability particularly, and their employability capital, generally. Moreover, misconceptions emerged about HEIs’ offerings concerning employability and tour-guides’ education. Conclusions. Employability capital has become a factor influencing success in the work environment. This study revealed the importance of practical courses in tourism education (tour guiding, first aid, and additional languages) and highlighted the imperative to understand students’ skills and capabilities within the scope of practical training courses. Originality. The study advances knowledge on employability capital in relation to tour guiding at WHS. This would help to develop a better system that would increase employability capital in the tour-guiding sector.